Yeast and microalgal symbiotic cultures using low-cost substrates for lipid production. (September 2019) - Dias, Carla; Santos, José; Reis, Alberto; Lopes da Silva, Teresa
Abstract: Some yeast and microalgae species are able to accumulate >20% of lipids (w/w) and have complementary nutritional requirements. The use of symbiotic (mixed or sequential) cultures of yeasts and microalgae show several advantages over pure cultures, and can be a strategy to enhance microbial lipid and carotenoid production, in comparison to pure cultures. In addition, if low cost substrates are used, such as industrial residues or effluents, the process costs may be reduced. This review presents an overview of different strategies of oleaginous yeast and microalgae symbiotic cultures for lipid production using low cost substrates, highlighting the major benefits and disadvantages of such strategies in comparison with pure cultures performance. Highlights: This review analyses the different strategies of oleaginous microbes co-cultures. It is aimed the use of low-cost substrates for lipid production. It is highlighted the benefits/disadvantages of such strategies. It is provided state-of-art information focusing on the latest developments.